Impact of sectors and political influence on financial distress across Pakistani public listed firms - Nabi, Agha Amad (2017)
Identifying financial distress provides information on ways to control and direct firms in achieving their goals. The common approach is to study the relationship between set of explanatory variables and financial distress. However, in order to improve the firms‘ financial structure, there is a need to understand the impact of sectors and different political conditions that affect financial distress. This study investigated the industry effects on financial distress as it is identified that financial distress might differ for firms due to the unique nature of each industry. The study dealt with projected key ideas to evaluate and compare diverse financial distress models to show the robustness of Pakistani listed firms across industries, and study how good financial distress can be predicted. Finally, to alleviate the severe consequences of political instability, the current study underlined the differences in financial distress determinants during different political regimes (Dictatorship and Democratic). The study analysed 153 non-financial firms listed on Karachi Stock Exchange (KSE) during a ten-year period (2004-2013) featuring two political periods; 2004 to 2008 as dictatorship period and 2009 to 2013 as democratic period. Four models were employed, namely logit analysis, decision tree, neural network and paired t-test. A diversity of models was employed to check the strength and prediction correctness of the models and t-test was employed to compare two different political regimes. From the findings, the indirect impact is clearly noticeable due to changes in the signs and magnitude of determinants across sectors. Logit analysis shows better results as compared to the other models as it was based on different industry-level variables and two different political regimes. The mechanism among the variables and financial distress is dependent on different political conditions of the country. The result shows that the impact of different political conditions varies across sectors. In addition, the results of this study are valuable for financial institutions to forecast financial distress and estimate minimum capital requirements to reduce the cost of risk management.